A Systematic Review of Effectiveness of Music Therapy on Depression In The Elderly - Nur Sayyid Jalaluddin Rummy; Windarti Rumaolat; Trihartuty Trihartuty (Universitas Airlangga, 2020)
ABSTRACTIntroduction: There are many non-pharmacological therapies in reducing symptoms of depression in older adult, one of which is music therapy. The aim of this article is to determine the effectiveness of the use of music therapy in reducing symptoms of depression in the elderly.Methods: A systematic approach was performed in this review using the PRISMA approach and journal sources from several databases including Scopus, ScienceDirect, SAGE, NCBI, CINAHL/EBSCO in the last 6 years from 2014 to 2019. Boolean operators were used within search process using AND and OR. The inclusion criteria are elderly aged ≥60 years with depression, either home or hospital treatment. Exclusion criteria are additional physical illness such as Diabetes Mellitus, CVA and other chronic diseases. Literature review, editorial, critical synthesis, and the like also become an exclusion criteria in this review.Results: Overall, the review consists of 13 articles with seven articles using RCT design, two quasi-experimental design, two pre-posttest design, and two exploratory design. In this review, several articles used an individual therapy and others a combination of music therapy with other activities such as singing, dancing and writing a lyric. Average time spent for a music therapy in elderly with depression was given from two weeks to six months, which may have been effective in making an impact. Every week had one or two sessions with a duration of30-60 minutes for every session.Conclusion: Music therapy is effective to reduce depression in the elderly.